Singular H∞ control - Astolfi,A (1994)
The present paper presents a solution to the singular H∞ control problem via state feedback for a class of nonlinear systems. It is shown that the problem of almost disturbance decoupling with stability plays a fundamental role in the solution of the considered problem. We also point out when the singular problem can be reduced to a regular one or solved via standard H∞ technique. We must stress that the solution of the singular problem is obtained without making any approximation of it by regular problems, i.e. via the so called cheap control. The latter is used to provide a solution to the general H∞ control problem, i.e. when no assumptions are made on the zero dynamic of the system.